2022
DOI: 10.3390/coatings12071015
|View full text |Cite
|
Sign up to set email alerts
|

Design Methodology and Application of Surface Texture: A Review

Abstract: Surface texture is regarded as a promising solution for enhancing the tribological features of industrial materials due to its outstanding benefits, such as minimization of the contact area, enhancement of the load bearing capacity, storage of the lubricant, and management of the transition between lubrication regimes. Surface texture can be processed under either liquid or gas conditions. As compared to laser ablation in air, employing liquids or other gases as ablation media provides high accuracy and unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 156 publications
0
14
0
Order By: Relevance
“…Microstructures on the surface of 40Cr13 are widely used in the die industry owing to their properties, such as being aesthetically appealing, tribological, and easy to detach from injection points [ 1 , 2 ]. However, it is difficult to precisely process the ideal microstructure on the surface of 40Cr13 because of its hardness and strength.…”
Section: Introductionmentioning
confidence: 99%
“…Microstructures on the surface of 40Cr13 are widely used in the die industry owing to their properties, such as being aesthetically appealing, tribological, and easy to detach from injection points [ 1 , 2 ]. However, it is difficult to precisely process the ideal microstructure on the surface of 40Cr13 because of its hardness and strength.…”
Section: Introductionmentioning
confidence: 99%
“…By conserving lubrication, trapping worn debris, reducing the contact surface and generating hydrodynamic pressure, micro-pits technology may enhance anti-seizing performance (Cai et al , 2022). Researchers have shown that the texture of the mating surface between two metals may have a significant effect on the impact of the interaction (Nsilani Kouediatouka et al , 2022). additional investigation in this study, Dawari et al (2022) applied a surface texturing technique to hard metal specimens with micro-pits at normal and high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The roughness height of the areas without dimples is also important. The pit area ratio seems to be the most important parameter of textured surfaces [ 3 ] and is typically between 5 and 25% [ 4 ]. Two-process cylinder liners with micro grooves are examples of textured surfaces [ 5 ].…”
Section: Introductionmentioning
confidence: 99%